Physics conditions for robust control of tearing modes in a rotating tokamak plasma. (23rd November 2017) - Lazzaro, E; Borgogno, D; Brunetti, D; Comisso, L; Fevrier, O; Grasso, D; Lutjens, H; Maget, P; Nowak, S; Sauter, O; Sozzi, C
Abstract: The disruptive collapse of the current sustained equilibrium of a tokamak is perhaps the single most serious obstacle on the path toward controlled thermonuclear fusion. The current disruption is generally too fast to be identified early enough and tamed efficiently, and may be associated with a variety of initial perturbing events. However, a common feature of all disruptive events is that they proceed through the onset of magnetohydrodynamic instabilities and field reconnection processes developing magnetic islands, which eventually destroy the magnetic configuration. Therefore the avoidance and control of magnetic reconnection instabilities is of foremost importance and great attention is focused on the promising stabilization techniques based on localized rf power absorption and current drive. Here a short review is proposed of the key aspects of high power rf control schemes (specifically electron cyclotron heating and current drive) for tearing modes, considering also some effects of plasma rotation. From first principles physics considerations, new conditions are presented and discussed to achieve control of the tearing perturbations by means of high power ( P EC ≥ P ohm ) in regimes where strong nonlinear instabilities may be driven, such as secondary island structures, which can blur the detection and limit the control of the instabilities. Here we consider recent work that has motivated the search for the improvement of some traditional control strategies, namely the feedback schemes based on strict phase tracking of the propagating magnetic islands.